A double blinded randomized study on safety and efficacy between ultra sound guided and palpatory methods of axillary brachial plexus block for forearm surgeries - Gupta, Amar Nath; Das, Kamala Kanta (Asian Journal of Medical Sciences, 2017)
Background: Regional anaesthesia like brachial plexus blocks are increasingly practiced now a day’s for forearm surgery. A major limitation of brachial plexus block which may lead to unplanned general anesthesia is inconsistent block. Conventional nerve localization techniques which rely on surface anatomical landmarks may not provide satisfactory anesthesia. Aims and Objectives: In recent years, real time ultrasound guidance has been introduced as an aid to nerve localization. This study was planned to test the hypothesis that the quality of the axillary brachial plexus blockade guided by ultrasound was better than those using surface anatomical landmarks and produced fewer adverse effects and overall success in cases of forearm surgeries. Materials and Methods: After obtaining institutional ethics committee approval and written informed consent, 100 patients of American Society of Anesthesiologists grade I or II scheduled for forearm surgeries were included in the study and were randomly allocated into two groups. The brachial plexus blockade via axillary approach guided by ultrasound and traditional nerve localization techniques which rely on surface anatomical landmarks, patient report of paresthesia, and/or elicitation of a motor response by mechanical nerve stimulator or electric nerve stimulation with single-injection method was carried out in the two groups of patients respectively. Results: The patients (n=100) predominantly female (55%) with comparable demographic profile found to have statistically insignificant changes in the mean pulse rate, blood pressure, respiratory rate changes and oxygen saturation of hemoglobin during the surgical operations. Overall block success rate, blockade of each individual target nerve was better and procedural hazards were less in the ultrasound guided group. Conclusion: Real time ultra sound guided axillary nerve block is better than traditional palpable method with lesser adverse outcome. Asian Journal of Medical Sciences Vol.8(2) 2017 69-75